A comparative study of catalogers' perceptions on the use of Bibliofile as a cataloging tool - Cruz, Annelyn G.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study focuses on the catalogers' perception on the use of BiblioFile as a cataloging tool. The study seeks to: 1) find out what features of BiblioFile are useful in the libraries under study; 2) know the perceptions of catalogers regarding BiblioFile; 3) know how satisfied the catalogers are with BiblioFile; 4) know the differences between BiblioFile and other cataloging tools; 5) point out the strengths and weakenesses of BiblioFile; and 6) give suggestions and recommendations which may be beneficial to the catalogers who are using it. The descriptive research method was used, with questionnaires and informal interviews.
The findings reveal that: 1) most libraries use only the cataloging module of BiblioFile; 2) their primary source of knowledge about BiblioFile came mostly from jobs and others, from the recommendations of their friends; 3) most of the respondents were able to perform searches immediately during their first experience with BiblioFile; 4) BiblioFile is easy to operate because the first time users were able to navigate through the software without much difficulty; 5) the catalogers found BiblioFile to be very useful for copy cataloging and retrospective conversion; 6) the biggest problems with BiblioFile are that its CDs are very prone to scratches; this contains very few Filipiniana titles; and BiblioFile is expensive; and 7) the respondents were happy with the performance of BiblioFile.
The study recommends the following: 1) the software should be properly installed to prevent errors; 2) ensure that all BiblioFile CDs are delivered completely and are free from damages; 3) academic libraries should form a cooperative in which they will pool their resources to buy a copy of BiblioFile to be shared by all the members of the cooperative; 4) BiblioFile can also be used for acquisition and circulation; 5) the developers should increase the number of Filipiniana materials contained in the software; 6) catalogers should remember that BiblioFile is just a tool and it will not work without the input from them; and 7) catalogers should also explore cataloging support systems.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: BiblioFile; Catalogers -- Philippines -- Manila Metropolitan Area